E-learning: Design strategies for promoting sustainable practices in paddy farming - Othman, Zakirah; Muhammad, Amran (2010)
Malaysia aims to transform its current agricultural practices to modern, innovative and sustainable levels.There are many issues highlighted to improve the sustainability of agricultural practices.However, this is not an easy task because there are several problems that the society and farmers will face, especially in enhancing their lifestyles as well as their ecosystems. Introducing Information and Communication Technology (ICT) application like electronic learning (e-learning) is a novel way to educate and promote the young generation to appreciate sustainable agriculture.Therefore, the main objective of this paper is to discuss a design of a prototype of persuasive learning in virtual paddy as a tool to promote sustainable practices in paddy farming.Before designing a prototype, the current practices of sustainable agriculture should be collected.After that, a pilot test will be conducted with the help of an expert user.